Co&De / Nursyamimi Busu ... [et al.] - Busu, Nursyamimi; Nik, Nurhidayah; Abdullah, Masturina; Wan Azmi, Wan Nurul Hazwani; Ali, Nurul Izzati; Firus, Ummi Aqilah; Abidin, Nurul Izzah (2021)
PRODUCT:Our business plan is to open a cafe named Co&De. Co&De cafe provides coffee and desserts to everyone, no matter who you are, where you are from, your skin color and your status. Why did we say, everyone? Our beverages not only have coffee but also chocolate so that the one that’s not into the coffee can have their drinks too. Our desserts not only had choices from local desserts but also foreign desserts. The same goes for the flavor. Some drinks contain spices for those who prefer them. Co&De not only sells the sweet flavor of desserts, just like the drinks, but some also contain spices, and some have savory flavor. CUSTOMERS: The target audience for Co&De cafe are those people that can afford to buy as our price is not that expensive like the hotel food. But that does not mean that we are using low-quality ingredients. It is just that we are going to find the best quality for all of the ingredients at the best price. Just like where our Co&De cafe is located, the target customer is also from the nearest area that will be our main target. As for the age range, of course, our main target will be the adults who are working already and have their own income. FUTURE OF THE COMPANY: Opening a cafe is a fast-paced evolving industry. In response to the future of this business plan and as the planner of Co&De cafe, we will try our best to find the better-quality ingredient at the lowest price so that the price will not exceed the planned price. Not only that we will be focusing on, the menu or choice of the desserts and drinks also will be updated from time to time. It is to ensure customers get to pick their various favorites. The taste also will be our main priority to be checked every single day so that customers do not get false hope. Co&De cafe will try their best to enlighten their customers’ whole day.